2020
DOI: 10.1039/d0bm01154a
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial-assisted photoimmunotherapy for cancer

Abstract: The biomaterials have been well designed as photoabsorbing/sensitizing agents or effective carriers to enhance the photoimmunotherapeutic efficacy and evade their side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Accumulating studies have indicated that various treatment methods, such as chemotherapy [16,17], photodynamic therapy (PDT), photothermal therapy (PTT) [18][19][20] and chemodynamic therapy (CDT) [21,22], can both kill tumors and activate the immune system by releasing tumor-associated antigens (TAAs) to stimulate the host's specific immune response to cancer, thus assisting ICB therapy [23,24]. For example, PDT utilizes photosensitizers and light to convert oxygen into reactive oxygen species (ROS) [25,26], which can induce immunogenic cell death (ICD) in cancer cells by exposing and releasing damage-associated molecular patterns (DAMPs) and subsequently convert the immunosuppressive microenvironment ("cold" tumors) into an immuneactivated microenvironment ("hot" tumors) [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have indicated that various treatment methods, such as chemotherapy [16,17], photodynamic therapy (PDT), photothermal therapy (PTT) [18][19][20] and chemodynamic therapy (CDT) [21,22], can both kill tumors and activate the immune system by releasing tumor-associated antigens (TAAs) to stimulate the host's specific immune response to cancer, thus assisting ICB therapy [23,24]. For example, PDT utilizes photosensitizers and light to convert oxygen into reactive oxygen species (ROS) [25,26], which can induce immunogenic cell death (ICD) in cancer cells by exposing and releasing damage-associated molecular patterns (DAMPs) and subsequently convert the immunosuppressive microenvironment ("cold" tumors) into an immuneactivated microenvironment ("hot" tumors) [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In certain cases, biomaterials themselves can act as phototherapy agents, amplifying the antitumor immunity induced by phototherapy. 113 PDT is a treatment method utilizing light irradiation at photosensitizer-accumulated sites, leading to the generation of ROS to treat tumors. An important aspect of PDT is its ability to rapidly release tumor cell debris, thereby triggering immunogenicity and ameliorating tumor antigen presentation via APCs.…”
Section: Acs Biomaterialsmentioning
confidence: 99%
“…261 If the responses are amplified, auxiliary methods such as immune checkpoint blockade (ICB) may also be available. 262 In this regard, different types of biomaterials have been served as photoabsorbers or sensitizing agents to improve the performance of the therapeutics as well as minimize the possible side effects of this new technique. For instance, the encapsulation of oligodeoxynucleotides inside chitosan-coated hollow copper sulfide (CuS) nanoparticles was an effective template as a photoabsorbent agent (Fig.…”
Section: Advanced Applications Of Polysaccharides In Biomedical Engin...mentioning
confidence: 99%